1984
DOI: 10.1017/s0025315400030149
|View full text |Cite
|
Sign up to set email alerts
|

Recolonization of a rocky shore in S.W. Ireland following a toxic bloom of the dinoflagellate, Gyrodinium aureolum

Abstract: Plate I, Figs, The mortalities and subsequent recolonization of a rocky shore in S.W. Ireland following a bloom of the toxic dinoflagellate, Gyrodinium aureolum in 1979 are described. Selective mortalities of key animal species notably grazing gastropods were followed by a marked increase in fucoid algae. Enteromorpha spp. blooms were a feature of vertical surfaces only. In general planktonic recruiting gastropods exhibited the most rapid recovery. Forty-two months after the red tide, fucoid algae still domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The connection between blooms of Gyrodinium aureolum and harmful effects on fish and bottom invertebrates is well documented (Braarud & Heimdal 1970, Helm et al 1974, Tangen 1977, Southgate et al 1984, Potts & Edwards 1987, Mahoney et al 1990. 'Present address: Marine Biological Laboratory (University of Copenhagen), DK-3000 Helsinger.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between blooms of Gyrodinium aureolum and harmful effects on fish and bottom invertebrates is well documented (Braarud & Heimdal 1970, Helm et al 1974, Tangen 1977, Southgate et al 1984, Potts & Edwards 1987, Mahoney et al 1990. 'Present address: Marine Biological Laboratory (University of Copenhagen), DK-3000 Helsinger.…”
Section: Introductionmentioning
confidence: 99%
“…Filter feeders were slowest to recovery, reaching levels equivalent to controls only in the fourth year. This sequence mirrors that described for the recovery of rocky shore following diverse disturbances, irrespective of whether the cause is oil spills (Peterson et al, 2000), dispersant used to clear oil (Southward and Southward, 1978;Hawkins and Southward, 1992), river floods (Branch et al, 1990), human harvesting of invertebrates , deposition of copper-mining waste tailings (Castilla, 1996), or toxic algal blooms (Southgate et al, 1984;Sasikumar et al, 1989).…”
Section: Discussionmentioning
confidence: 54%
“…Following a harmful algal bloom in India, Sasikumar et al (1989) noted that immediate elimination of most grazers led to a bloom of ephemeral alga Enteromorpha, later replaced by Dictyota dichotoma Hudson. Southgate et al (1984) similarly recorded that bloomrelated elimination of grazers (notably limpets) led to development of dense algal growths that persisted for at least four years. Kim (1997) has experimentally shown that early succession of rocky shores in British Columbia, Canada, is dominated by ephemeral algae in the absence of limpets, and that ephemerals inhibit the development of later-succession algae under these conditions.…”
Section: Discussionmentioning
confidence: 92%
“…in the horse mussel Modiolus modiolus and saddle oyster (Family Anomiidae), whereas the common mussel Mytilus edulis and the edible oyster Ostrea edulis appeared to be resistant , Underdal et al 1989, Pedersen et al 1992. Selective mortality of littoral fauna was also reported by Southgate et al (1984) from SW Ireland following a bloom of the toxic dinoflagellate Gyrodinium aureolum. In soft sediments toxic effects and mass mortalities of lugworm populations Arenicola marina in South Wales, also related to a bloom of G. aureolum, were described by Olive & Cadnam (1990).…”
Section: Possible Mechanisms Of Impact Frommentioning
confidence: 98%